(untitled) - Gerrish, Brian Albert; (1931-...) (Great Britain, 1982)
In recent years, much of the best historical work on the Reformation has been directed at Luther and his medieval background. It is B. A. Gerrish's contention, however, that the significance of Protestant ideas cannot be appraised historically if Luther is made the sole point of reference or if the Reformation is treated as something other than a critical moment in a larger historical development to which liberal Protestantism also belongs. Nor, he maintains, can ideas and doctrines be understood in abstraction from the religious experience they express.
Keywords: Theology, Doctrinal -- History